Elective Fenestrated and Branched Endovascular Thoraco-abdominal Aortic Repair with Supracoeliac Sealing Zones and without Prophylactic Cerebrospinal Fluid Drainage: Early and Medium-term Outcomes. (May 2019) - Juszczak, Maciej T.; Murray, Anna; Koutsoumpelis, Andreas; Vezzosi, Massimo; Mascaro, Jorge; Claridge, Martin; Adam, Donald J.
Abstract : Objective: To report the outcome of elective fenestrated and branch (FEVAR–BEVAR) endovascular aortic repair with supracoeliac (SC) sealing zones and the impact of staged repair without prophylactic cerebrospinal fluid (CSF) drainage on the incidence of spinal cord ischaemia (SCI). Methods: Two hundred and seventy consecutive patients (217 men; mean [SD] age, 72.8 ± 6.3 years; median (IQR) diameter 65 mm [62–75 mm]) with juxtarenal (JRAAA) ( n = 69) or thoraco-abdominal aortic aneurysms (TAAAs) ( n = 201) underwent elective FEVAR ( n = 192) or BEVAR ( n = 78) with renovisceral stent grafting, proximal SC (Zones 1–5; <40 mm [ n = 83]; ≥40 mm [ n = 187]) and distal infrarenal aorto-iliac sealing zone (Zones 9–11) between December 2008 and September 2017. A spinal cord protection protocol (SCPP) including staging without prophylactic CSF drainage was introduced in September 2012. Results: A total of 1026 renovisceral vessels (mean 3.8 ± 0.5 per patient) were targeted for preservation. One patient (0.4%) died in the institution within 30 days and 31 (11.4%) developed 36 major non-fatal complications including unplanned permanent dialysis ( n = 1, 0.4%) and non-ambulatory SCI ( n = 6, 2.2%). In patients with <40 mm SC coverage, none were staged or had prophylactic CSF drains and none developed SCI. In patients with ≥40 mm SC coverage, SCI occurred in 3.3% (pre-SCPP: 4/20 [20%; none staged, 13 prophylactic CSF drains] vs. post-SCPP: 2/167 [1.2%; 89 staged, no prophylactic CSF drains]; p = .001 [OR = 19.9]). Estimated survival (±SE) at one, two and three years was 92.6% ± 1.6%, 86.5% ± 2.4%, and 73.8% ± 3.5%, respectively, with no significant difference comparing extent of aneurysm or SC coverage. Forty-three (15.9%) patients required late re-intervention. Estimated freedom from re-intervention at one, two and three years was 91.9% ± 1.8%, 85.1% ± 2.5%, and 79.5% ± 3.2%, respectively. Conclusion: Elective endovascular thoraco-abdominal aortic repair with SC sealing zones can be performed with low peri-operative risk and good medium-term outcomes. Selective staging without prophylactic CSF drainage contributed to a significant reduction in the incidence of SCI.